2021
DOI: 10.7759/cureus.14020
|View full text |Cite
|
Sign up to set email alerts
|

Serosurveillance of Health Care Workers in a COVID Hospital: Immune Response, and Its Longevity

Abstract: Objective: We aimed to study the seroprevalence of coronavirus disease 2019 (COVID-19) and sustainability of the immune response in health care workers (HCWs). A cross-sectional study was conducted between October 7 and November 30, 2020, in a multi-specialty hospital in Eastern India designated as COVID hospital during this pandemic. Study participants included 2,110 HCWs, including those who have recovered from COVID infection. Method: HCWs were required to complete a questionnaire and give written consent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
5
2
2
Order By: Relevance
“…The maximum number of SARS-CoV-2 infected persons (87.9%) had positive IgG antibodies after 2 months of infection; however, it declined to 50% after 4 months which explained short-lived protective immunity and the possibility of reinfection. 40 In contrast to our findings, a study from Italy suggests that reinfections are rare events and patients who have recovered from COVID-19 have a lower risk of reinfection for a year. 41 …”
Section: Discussioncontrasting
confidence: 99%
“…The maximum number of SARS-CoV-2 infected persons (87.9%) had positive IgG antibodies after 2 months of infection; however, it declined to 50% after 4 months which explained short-lived protective immunity and the possibility of reinfection. 40 In contrast to our findings, a study from Italy suggests that reinfections are rare events and patients who have recovered from COVID-19 have a lower risk of reinfection for a year. 41 …”
Section: Discussioncontrasting
confidence: 99%
“…A study from Maharashtra found only 1.6% asymptomatic HCWs as RT-PCR positive [ 26 ]. The seropositivity among HCWs detected by the study from eastern India was comparable to our findings [ 27 ]. We found a significantly higher level of seropositivity ( p ​= ​ 0.005 ) as well as viral carriage ( p ​= ​ 0.004 ) amongst the HCWs than in non-HCWs.…”
Section: Discussionsupporting
confidence: 90%
“…63 studies were excluded, resulting in a total of 53 studies (Babu et al, 2020;George et al, 2021;Ghose et al, 2020;Ghosh et al, 2021;Goenka et al, 2020;Ramasamy S, 2021;Gupta et al, 2021;Inbaraj et al, 2021;V. Jain et al, 2021;Jessy et al, 2021;Joshi et al, 2021;Kar et al, 2021;Kerala, 2021; M. S. Khan et al, 2021; S. M. S. Khan et al, 2020;Kshatri, 2021;Kshatri et al, 2021; M. S. Laxmaiah et al, 2021;Madhusudan et al, 2021;Mahto et al, 2021;Makadia et al, 2021;Malani, Ramachandran, et al, 2021;Malani, Shah, et al, 2021;Mishra et al, 2021;Mohanan et al, 2021;M. Murhekar et al, 2020; M. V. M.…”
Section: Selection Of Studiesunclassified